Building A Moderate Muslim Diversity Through Digital Islamic Counseling - Lutfiani, Erfa Noni; Wildany, Zidna Naufan; Mu’alim, Miftakhul Aden; Puspitasari, Yahya Agus; Sa’adah, Zahwa Aliya; Azzahro, Audy Fia; Zakirah, Luluk Alfina; Lathifah, Luthfatul (International Tatho Academics, 2025)
This study aims to identify the value of religious moderation in the content of the counselling programme ‘Becoming a Muslim, Becoming Tolerant’ by M. Shofi Falikul Isbach. Qualitative data was collected from articles, videos, and social media posts related to religious moderation. The findings of this study confirm that religious moderation can be integrated through non-academic activities and the use of social media. The study concludes that both approaches effectively disseminate values of tolerance and anti-radicalism to society, particularly among the younger generation.. The study underscores that the dissemination of moderate Islamic religious values can be internalised through digital counselling media.